Pelatihan Manajemen Pengelolaan Emosi pada Ibu-Ibu PKK RT.02/RW.05 Gemah Pedurungan Semarang - Rusmalia Dewi; Gusti Yuli Asih; Yudi Kurniawan; Agung Santoso Pribadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The goal of this community service (PkM) program is to provide Emotion Management training to the PKK mothers to enhance their understanding of the importance of self-compassion related to emotions, in order to support physical and mental health. The training includes relaxation techniques, effective communication, and problem-solving that help individuals manage their emotions in daily interactions. Relaxation techniques are used to improve subjective well-being and promote a healthy lifestyle that benefits both themselves and their environment. Most of the PKK mothers in RT.02/RW.05 of Kelurahan Gemah are housewives who face pressures from family and social environments. Emotional management is crucial to prevent negative impacts on mental health, which can affect both the family and the community. Therefore, the PkM team from the Faculty of Psychology conducts training to help the mothers manage their emotions. The training activities include lectures, storytelling, games, and discussions. As a result, there was a 40% improvement in their understanding of emotion management. Through this training, it is hoped that the mothers will find it easier to control their emotions, focus, and better understand themselves and their environment, thus enabling them to overcome challenges in their daily lives.